Edukasi Media Sosial Sebagai Alat Pemasaran Bagi Wirausaha Pemula Gerakan Pemuda Ansor Kecamatan Pagedangan - Aldila Rahma Putri; Jaenudin Jaenudin; Ahyani Ahyani (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This Community Service (PKM) activity aims to improve the understanding, knowledge, and skills of novice entrepreneurs in utilizing social media as a digital marketing tool to expand market reach and increase business competitiveness. The activity implementation method uses an educational and participatory approach through initial surveys, counseling, training, demonstrations, direct practice, discussions, questions and answers, mentoring, and evaluations. The activity was carried out on April 18–19, 2026, involving novice entrepreneurs, the community, and young people who have an interest in entrepreneurship. The results of the implementation showed that participants experienced an increased understanding of digital marketing concepts, were able to manage business social media accounts better, and had skills in creating more attractive and effective promotional content. Furthermore, participants gained a deeper understanding of the importance of branding strategies, customer interaction, and the use of social media to expand their market. This PKM program positively contributes to improving digital literacy, encouraging technology-based marketing transformation, and strengthening the competitiveness of budding entrepreneurs in the digital economy era.